2017
DOI: 10.1103/physrevd.96.123508
|View full text |Cite
|
Sign up to set email alerts
|

Novel approach toward the large-scale stable interacting dark-energy models and their astronomical bounds

Abstract: Stability analysis of interacting dark-energy models generally divides its parameters space into two regions, (i) w x ≥ −1 and ξ ≥ 0 and (ii) w x ≤ −1 and ξ ≤ 0, where w x is the dark-energy equation of state and ξ is the coupling strength of the interaction. Because of this separation, crucial information about the cosmology and phenomenology of these models may be lost. In a recent study, it has been shown that one can unify the two regions with a coupling function that depends on the dark-energy equation of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
63
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 93 publications
(70 citation statements)
references
References 107 publications
(147 reference statements)
7
63
0
Order By: Relevance
“…It is important to mention that the division of the parameter space into (ξ < 0, w x < −1) or (ξ > 0, w x > −1) is motivated from the doom factor analysis [14]. Following the notation of [26,27,40], the doom factor d is defined as…”
Section: Observational Data and Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to mention that the division of the parameter space into (ξ < 0, w x < −1) or (ξ > 0, w x > −1) is motivated from the doom factor analysis [14]. Following the notation of [26,27,40], the doom factor d is defined as…”
Section: Observational Data and Methodologymentioning
confidence: 99%
“…We refer to Refs. [27,31,34,40,41] for details concerning the linear perturbation theory within these coupled cosmologies.…”
Section: Interacting Dark Universementioning
confidence: 99%
“…It has been found that the presence of an interaction in the dark sector could successfully reconcile the long lasting cosmic coincidence problem [3,4,5,6,7]. Following this, a number of investigations in the context of interacting DE -DM models were performed by many investigators [8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43] (also see two review articles in this direction [44,45]). An interesting outcome from the interaction is that, it could naturally explain the phantom dark energy equation-ofstate [46,47,48,49].…”
Section: Introductionmentioning
confidence: 99%
“…[48,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63]). Although within most dark sector models the two dark components do not interact, an interesting class of cosmological models (usually referred to as coupled DE) feature interactions between DM and DE (see for example [64,65,66,67,68,69,70,71,72,73,74,75,76,77,78,79,80,81,82,83,84,85,86,87,88,89,90,91,92,93,94,95,96]). While we cannot do justice to the enormous literature on dark sector models, it is clear from the discussion so far that there is no shortage o...…”
Section: Introductionmentioning
confidence: 99%